Androgen-Targeted Therapy-Induced Epithelial Mesenchymal Plasticity and Neuroendocrine Transdifferentiation in Prostate Cancer: An Opportunity for Intervention - Nouri, Mannan; Ratther, Ellca; Stylianou, Nataly; Nelson, Colleen C.; Hollier, Brett G.; Williams, Elizabeth D. (Frontiers in Oncology, 2014)
Androgens regulate biological pathways to promote proliferation, differentiation and survival of benign and malignant prostate tissue. Androgen receptor targeted therapies exploit this dependence and are used in advanced prostate cancer to control disease progression. Contemporary treatment regimens involve sequential use of inhibitors of androgen synthesis or androgen receptor function. Although targeting the androgen axis has clear therapeutic benefit, its effectiveness is temporary, as prostate tumor cells adapt to survive and grow. The removal of androgens (androgen deprivation) has been shown to activate both epithelial-to-mesenchymal transition (EMT) and neuroendocrine transdifferentiation programs. EMT has established roles in promoting biological phenotypes associated with tumor progression (migration/invasion, tumor cell survival, cancer stem cell-like properties, resistance to radiation and chemotherapy) in multiple human cancer types. Neuroendocrine transdifferentiation in prostate cancer is associated with resistance to therapy, visceral metastasis and aggressive disease. Thus, activation of these programs via inhibition of the androgen axis provides a mechanism by which tumor cells can adapt to promote disease recurrence and progression. Brachyury, Axl, MEK and aurora kinase A are molecular drivers of these programs, and inhibitors are currently in clinical trials to determine therapeutic applications. Understanding tumor cell plasticity will be important in further defining the rational use of androgen targeted therapies clinically and provides an opportunity for intervention to prolong survival of men with metastatic prostate cancer.